Analysis of the dental status of patients with type 1 and 2 diabetes mellitus - I. O. Pohodenko-Chudakova; E. V. Maksimovich; Y. O. Kuznetsov; N. L. Gustodym; U. V. Shpetnaya (Military Medicine, 2026)
Introduction. As of 01.01.2024, 379,510 patients with diabetes were under medical supervision in the Republic of Belarus, including 19,252 with type 1 diabetes and 356,396 with type 2 diabetes. The annual increase in the number of patients is 5.0–8.0 %. The aim of the work is to compare the dental status of patients with type 1 and type 2 diabetes. Materials and methods. A retrospective analysis of outpatient dental records of patients undergoing outpatient follow-up with an endocrinologist for type 1 and type 2 diabetes mellitus was performed. Patients with type 1 diabetes mellitus (19 patients) made up group 1, which was divided into two subgroups 1.1. – type 1 diabetes without complications (9 patients), 1.2. – type 2 diabetes with complications (10 people); with type 2 diabetes mellitus (20 patients) – group 2, which It was also divided into two subgroups 2.1. – Type 2 diabetes without complications (10 patients), 2.2. – Type 2 diabetes with complications (10 patients). Results. It was de termined that destructive changes in the periodontium with tooth loss prevail in patients with type 2 diabetes, and a greater number of foci of chronic odontogenic infection were identified, which may indicate a greater lesion of the bone structures of the maxillofacial region in people with type 2 diabetes mellitus compared with patients with type 1 diabetes. Conclusion . The revealed facts should be taken into account when planning therapeutic and preventive measures for patients of this category.